Optimization of generator reactive power dispatch - Toque, Vida Joan Gumera-
This paper proposes a generator Reactive Power Dispatch Optimization (RPDO) method that uses generator reactive power outputs to maintain bus voltages, and line flows within limits. The proposed scheduling of generator reactive power is decoupled from the real power scheduling, similar to the current practice in the Philippine electric power industry where the energy schedules are pre-determined in the Wholesale Electricity Spot Market (WESM). The reactive power dispatch was formulated as an optimal power flow (OPF) problem with generator reactive power and power factor constraints. The objective function of the optimization is to minimize the total reactive power support (RPS) cost to be paid by the system operator, based on the approved guidelines for RPS compensation in the Ancillary Services Procurement Plan (ASPP) and the Philippine Grid Code (PGC). The methodology was tested on the IEEE 30 bus test system and the aggregated Visayas network model. Results of the simulation using the Visayas grid showed that during peak loading condition, by scheduling the reactive power outputs of the available on-line generators, the bus voltages were successfully kept within limits. The RPDO was simulated using eight different loading levels based on the 2012 historical data of the Visayas grid. As load levels increase, the number of generators operating at the PGC limits (0.85 lag or 0.9 lead) also increased. At low load levels, no RPS was required by the RPDO. In higher loading levels, the RPDO required at least one generator to operate beyond the PGC limits and provide RPS. Based on the results of the simulations, potential criteria for measuring the value of a generator's reactive power output to the system were presented. These criteria can help the system operator to determine which generators should be chosen for long-term ancillary services contracts.